Submicron Ti2CTx MXene particulates as high-rate intercalation anode materials for Li-ion batteries. Issue 29 (1st July 2022) - Cui, Cong; Dai, Ruqiao; Zhang, Chao; Fan, Bingbing; Wang, Xiaohui
Abstract : Submicron Ti2 CT x MXene particulates were prepared by etching Ti2 AlC synthesized by the molten salt method. The particulates without further modification attain an excellent rate performance as high as ∼155 mA h g −1 at a current density of 10 A g −1 . Abstract : Ever increasing demands for portable electronics and electric vehicles critically require high-rate Li-ion batteries (LIBs) whose performance fundamentally depends on electrode materials. However, currently commercialized anode materials including graphite and silicon fail to fulfill the higher requirement because of their intrinsically inferior rate capability. Here, we report submicron Ti2 CT x (s-Ti2 CT x ) MXene particulates as a high-rate intercalation anode material for LIBs. The particulates are derived from the layered ternary Ti2 AlC MAX phase that is readily fabricated by the molten salt method. The synthesized s-Ti2 CT x particulates have a high specific capacity of ∼155 mA h g −1 even at a high current density of 10 A g −1, exhibiting high rate capability. Specifically, the particulates, with a nominal chemical formula of Ti2 CT x Li1.4, can release ∼57% of their revisable capacity (∼270 mA h g −1 ) in 56 s and they exhibit good capacity retention during 1000 cycles. As evidenced by comprehensive electrochemical characterization studies, a reduction in the lateral size of MXene particulates remarkably facilitates an interlayer (de)lithiation process compared with their large counterparts. The s-Ti2 CT x also offers an opportunity to fabricate flexible electrodes with outstanding rate performance and cyclability. Our results provide a platform for studying MXene-based intercalation anode materials with desired electrochemical performance for high-rate LIBs.